An Analysis of Translations Techniques by Using (GT) Google Translate’s English into Indonesia in English Simple Sentences - Abd. Syakur; Sulistyaningsih Sulistyaningsih (Jurnal Basicedu, 2022)
The goal of this study was to examine the correlation between the accuracy and acceptability or also readability of Google Translation’s (GT) English to Bahasa Indonesia translations of simple English sentences. This study applied a correlational quantitative research approach using survey research. The samples of this study included all students majoring in the English Language Education Study department of the fourth semester and used a purposive sample technique of around 35 students from STKIP PGRI Sidoarjo. The results showed 3 sentences rated ‘very accurate’ (6%). 29 sentences (58%) were deemed ‘accurate’. Then, 11 sentences were ‘less accurate’ (22%). Lastly, 7 sentences (14%) were deemed ‘not accurate’. Furthermore, based on the SPSS 26 results showed the positive constant value of 78.884 indicates positive effect of independent variable (GT translation). If the independent variable changes by one unit, so will the GT translation variable. If GT translation (X) rises by one unit, questionnaire results (Y) rise by 0.324, or 32.4%. Regarding to the findings, translation using GT through basic English sentences on selected reading texts utilized at STKIP PGRI Sidoarjo was mainly positive (64%). The investigation revealed a remarkable occurrence that GT’s translations were mostly accurate.